Vyākaraṇamahābhāsyam = Patañjali's Vyākaraṇa Mahābhāṣya - Patañjali Grammatiker ca. v2. Jh; Kaiyaṭa ca. 11. Jh; Nāgeśabhaṭṭa; Bhaṭṭojī Dīkṣita ca. 17. Jh; Śāstrī, Guruprasāda
Classical exegesis of Pāṇini's Aṣṭādhyāyī, aphoristic work on Sanskrit grammar; includes commentaries and supercommentaries